2022
DOI: 10.1103/physrevb.106.174418
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous sign inversion of spin-orbit torque in ferromagnetic/nonmagnetic bilayer systems due to self-induced spin-orbit torque

Abstract: Self-induced spin-orbit torques (SI-SOTs) in ferromagnetic (FM) layers have been overlooked when estimating the spin Hall angle (SHA) of adjacent nonmagnetic (NM) layers. In this work, we observe anomalous sign inversion of the total SOT in the spin-torque ferromagnetic resonance due to the enhanced SI-SOT, and successfully rationalize the sign inversion through a theoretical calculation considering the SHE in both the NM and FM layers. The findings show that using an FM layer whose SHA sign is the same as tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 52 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…In addition, in HM/FM bilayers, the self-torque in the FM layers could counteract the torque generated by the HM layer, resulting in a reduced net torque. Taking advantage of the self-torques in the FM layer, making them work in conjunction with other SOTs instead, could lead to an increase in the SOT efficiency [3]. Tailoring the FM interfaces to change the self-torque direction and strength, in conjunction with searching for different materials as SOT sources, could be a promising route towards an increase in SOT efficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, in HM/FM bilayers, the self-torque in the FM layers could counteract the torque generated by the HM layer, resulting in a reduced net torque. Taking advantage of the self-torques in the FM layer, making them work in conjunction with other SOTs instead, could lead to an increase in the SOT efficiency [3]. Tailoring the FM interfaces to change the self-torque direction and strength, in conjunction with searching for different materials as SOT sources, could be a promising route towards an increase in SOT efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Also, electrical measurements on Py capped with SiO 2 or Al 2 O 3 show the presence of field-like and damping-like torques in Py devices [37]. And in metallic bilayers, it was shown that self-induced torques lead to errors in the estimation of the spin-torque strength [3]. These self-torques in ferromagnetic materials make it difficult to accurately determine to what extent the TMD layer is contributing to the SOT [37].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the SOT, spin current generated by the spin Hall effect (SHE) in the bulk of nonmagnetic metals, due to interface SOI (ISOI) and/or topological surface states, flows into an adjacent ferromagnetic material (FM), resulting in magnetization reversal. SOT has been demonstrated in a variety of systems, such as heavy metal/FM, , topological insulator/FM, , 2D material heterostructures, and even single FM layers without adjacent materials, , the latter referred to as self-induced SOT (SI-SOT). Despite the significant potential of SOT, its practical application in spintronic devices such as nonvolatile memory devices, oscillators, and domain-wall memories is still limited by the challenge of controlling its magnitude and orientation.…”
mentioning
confidence: 99%